2006
DOI: 10.1080/01926230601080502
|View full text |Cite
|
Sign up to set email alerts
|

Translocation Pathway of the Intratracheally Instilled Ultrafine Particles from the Lung into the Blood Circulation in the Mouse

Abstract: Recently, it has been demonstrated that ultrafine particles (UFPs) are able to translocate from the lung into the systemic circulation. Precise mechanisms of the anatomical translocation (crossing the air-blood barrier) of inhaled UFPs at the alveolar wall are not fully understood. In this study, we examined the translocation pathway of the intratracheally instilled ultrafine carbon black (UFCB) from the lung into the blood circulation in mouse. Electron microscopy demonstrated accumulation of intratracheally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
97
3
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(104 citation statements)
references
References 35 publications
1
97
3
3
Order By: Relevance
“…The following nanoparticles have been reported to be translocated at the ABB in association with endocytosis in vivo: gold particles (Furuyama et al 2009;Takenaka et al 2006); carbon particles (Shimada et al 2006); and C60 fullerene particles (Naota et al 2009). In in vitro experiments, internalization of 500 nm-sized latex breads (Rejman et al 2004) and 60 nmsized polystyrene particles (Xia et al 2008) by caveolaemediated endocytosis has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The following nanoparticles have been reported to be translocated at the ABB in association with endocytosis in vivo: gold particles (Furuyama et al 2009;Takenaka et al 2006); carbon particles (Shimada et al 2006); and C60 fullerene particles (Naota et al 2009). In in vitro experiments, internalization of 500 nm-sized latex breads (Rejman et al 2004) and 60 nmsized polystyrene particles (Xia et al 2008) by caveolaemediated endocytosis has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, at the same time, NP can directly interact with circulatory cells such as erythrocytes, leukocytes or platelets and potentially induce undesirable toxicity [4,5,6,7]. Therefore, investigation of the direct impact of SiNP on erythrocytes is needed, and will help to understand the possible pathophysiological effects of those particles on erythrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Values of SNARK mRNA expressions were normalized to -actin mRNA expression; C -control; n = 3; * -P < 0.05 [15]. Shimada et al [49] demonstrated that the intratracheally instilled ultrafine nanoparticles are able to translocate from the mouse lung into systemic circulation. Precise mechanisms of the anatomical translocation (crossing the air-blood barrier) of inhaled nanoparticles at the alveolar wall are not fully understood.…”
Section: Snark Kinase As a Stress Sensor And Sensitive Marker Of Silvmentioning
confidence: 99%